2015
DOI: 10.1590/1516-1439.349914
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cryogenic Treatment on the Corrosion of AISI D3 Steel

Abstract: It is well known that cryogenic treatment is used to improve the mechanical properties of a material. Consequently, the use of cryogenic treatment has grown beyond its successful application on tool steels. In this research, the effects of cryogenic treatment on the corrosion of AISI D3 steel in 3.5% NaCl solution were examined by electrochemical impedance spectroscopy (EIS). The surface structure of the AISI D3 steel was examined by scanning electron microscopy (SEM) after the EIS investigations. Results clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…These results show that wear in the presence of a corrosive medium for martensitic stainless steel DIN 1.4110 is an aggressive condition for the material's integrity. Since chloride-containing media are very common in cutlery and the food industry 24 , wear can strongly compromise the components' integrity. Dodds et al 9 studied wear on a friction stir welding process applied on martensitic AISI 420 stainless steel.…”
Section: Tribocorrosion Behaviormentioning
confidence: 99%
“…These results show that wear in the presence of a corrosive medium for martensitic stainless steel DIN 1.4110 is an aggressive condition for the material's integrity. Since chloride-containing media are very common in cutlery and the food industry 24 , wear can strongly compromise the components' integrity. Dodds et al 9 studied wear on a friction stir welding process applied on martensitic AISI 420 stainless steel.…”
Section: Tribocorrosion Behaviormentioning
confidence: 99%
“…This operation has involved hardening and tempering ( Fig. 1) [16,17]. The PCE-778 Laser Thermometer is a device used to measure temperature using an infrared laser at a specified distance.…”
Section: Field Studies (Piercing Experiments)mentioning
confidence: 99%
“…The applications of this treatment are extended to other materials [11]. Ilyas Uygur et al (2015) used electrochemical impedance analysis to study the corrosion resistance of D3 steel, using NaCl environment, and they observed significant improvements in corrosion resistance [12]. Potentiodynamic analysis and electrochemical impedance analysis are widely used to analyze the corrosion resistance of welded joints.…”
Section: Introductionmentioning
confidence: 99%